Buying Brands at Both Regular Price and on Promotion over Time. Issue 4 (November 2017) - Scriven, John; Clemente, Maria; Dawes, John; Trinh, Giang; Sharp, Byron
We analyse the purchasing of brands at both regular and promotional price over time. The goal is to better understand the extent of consumer deal-proneness. Our analysis shows most consumers buy brands on promotion at least some of the time, and the tendency to buy on promotion relates mostly to how much promotion is available in a category, suggesting little innate deal-proneness. The extent of promotion can be so high that as many as half of all brand buyers buy the brand solely when it is on promotion. However, this amount of on-deal buying is only very slightly higher than would be expected given the amount of promotion available. We find few buyers buy only on promotion. Promotion buyers of a particular brand also buy other brands on and off promotion more or less in line with the market share those other brands have at regular and promotional price. The three main implications are: (1) brand loyalty is still an important aspect of purchase, (2) a brand's normal-price buyers are a major source of its volume from price promotions, and (3) there is only a small effect of deal-proneness on promotion buying over and above that of promotion prevalence in a category.